Stock market liquidity and the decision to repurchase - Brockman, Paul; Howe, John S.; Mortal, Sandra (Journal of Corporate Finance, 2008)
We examine the impact of stock market liquidity on managerial payout decisions. We argue that stock market liquidity influences payout policy through a first-order effect on the share repurchase decision, and a second-order or residual effect on the dividend decision. Managers compare the tax and flexibility advantages of a repurchase against its liquidity cost disadvantage. All else equal, higher market liquidity encourages the use of repurchases over dividends. Our empirical results confirm that stock market liquidity plays a significant role in repurchase and dividend initiations, as well as in recurring payout decisions. Unlike previous studies that measure liquidity changes following the repurchase decision, we examine liquidity levels prior to the payout decision. We show that managers condition their repurchase decision on a sufficient level of market liquidity, consistent with Barclay and Smith's [Barclay, M.J., Smith, C.W. Jr., 1988. Corporate payout policy: cash dividends versus open-market repurchases. Journal of Financial Economics 22, 61–82.] theoretical analysis and Brav et al.'s [Brav, A., Graham, J.R., Campbell, R.H., Michaely, R., 2005. Payout policy in the 21st century. Journal of Financial Economics 77, 483–528.] CFO survey results. Repurchases have recently become the payout decision of choice in part because of rising stock market liquidity.